Behavior and nutritional condition buffer a large‐bodied endotherm against direct and indirect effects of climate. Issue 3 (1st August 2014) - Long, Ryan A.; Bowyer, R. Terry; Porter, Warren P.; Mathewson, Paul; Monteith, Kevin L.; Kie, John G.
Abstract : Temporal changes in net energy balance of animals strongly influence fitness; consequently, natural selection should favor behaviors that increase net energy balance by buffering individuals against negative effects of environmental variation. The relative importance of behavioral responses to climate‐induced variation in costs vs. supplies of energy, however, is uncertain, as is the degree to which such responses are mediated by current stores of energy. We evaluated relationships among behavior, nutritional condition (i.e., energy state), and spatiotemporal variation in costs vs. supplies of energy available to a large‐bodied endotherm, the North American elk ( Cervus elaphus ), occupying two ecosystems with contrasting climates and energy landscapes: a temperate, montane forest and an arid, high‐elevation desert. We hypothesized that during spring through autumn, behavioral responses to the energy landscape would be both context dependent (i.e., would vary as a function of the contrasting environmental conditions experienced by elk in the forest vs. the desert), and state dependent (i.e., would vary as a function of the energy balance of an individual). We tested several predictions derived from that hypothesis by combining output from a biophysical model of the thermal environment with data on forage quality, animal locations, and nutritional condition of individuals. At the population level, elk in the desert selected areas that reduced costs of thermoregulation over those that provided the highest‐quality forage. In the forest, however, costs imposed by the thermal environment were less pronounced, and elk selected areas that increased access to high‐quality forage over those that reduced costs of thermoregulation. At the individual level, nutritional condition did not influence strength of selection for low‐cost areas or high‐quality forage among elk in the forest. In the desert, however, strength of selection for low‐cost areas (but not forage quality) was state dependent; individuals in the poorest condition at the end of winter showed the strongest selection for areas that reduced costs of thermoregulation during spring and summer, and also expended the least amount of energy on locomotion. Our results highlight the importance of understanding the roles of behavior and nutritional condition in buffering endotherms against direct and indirect effects of climate on fitness.